IMPLEMENTASI PENDEKATAN PSIKOLOGI KOGNITIF DALAM PEMBELAJARAN PAI DI SMAN 1 SALATIGA - Taqiyya, Hedona Hilwa; Adzim, Fauzan; Mazfi'ah, Putri; Mufiq (LPPM STAI Muhammadiyah Probolinggo, 2026)
The lack of exploration regarding the application of cognitive psychology in Islamic Religious Education and the gap between learning theory and practice form the background of this study. This study aims to identify cognitive psychology-based learning strategies, understand the perceptions of teachers and students, and analyze the challenges and opportunities in their implementation at SMAN 1 Salatiga. The method used in this study was a qualitative case study with subjects consisting of 3 PAI teachers and six 11th grade students. Data were collected through in-depth interviews, participatory observation, and documentation studies, which were then analyzed thematically. The results of the study show that teachers apply cognitive load management strategies, dual coding using visual-verbal media, cognitive elaboration through discussion and presentation, and emotion management in learning. The perceptions of teachers and students tend to be positive towards increased motivation and understanding of the material. However, there were challenges faced, such as the heterogeneity of student abilities, the complexity of abstract material, emotional instability, and limited digital infrastructure. This study concluded that the application of cognitive psychology can effectively improve students' conceptual understanding, but requires systematic support from the school. These findings contribute to the development of an evidence-base PAI learning model.